TRIPS-past to TRIPS-plus: Upholding the balance between exclusivity and access - James Bacchus (Centre for International Governance Innovation (CIGI), 2021)
A deadly global pandemic and other unique circumstances have combined to present the World Trade Organization (WTO) with an opportunity to modernize its rules for the trade-related aspects of intellectual property (IP) rights. The best place to begin is with a full realization of the negotiated balance between exclusivity and access in the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement). There is the need to turn the "TRIPS-past" of WTO IP rules agreed in 1995 into the "TRIPS-plus" of improved rules more fit to purpose for the twenty-first century. New rules are needed to help spark new innovations of all kinds and the rapid spread of those innovations worldwide, including rules relating to intangible assets and especially to digital expressions of IP. Continuing questions over the extent to which the TRIPS Agreement protects the exclusivity of IP rights in COVID-19 vaccines underscore how much uncertainty remains about where the line of this balance is in this multilateral trade agreement, and also how much doubt still exists about whether that line is in the right place.
Keywords: 330